Variation in origin of the long head of the biceps brachii tendon in a cadaver: A case report. Issue 20 (May 2018) - Katsuki, Shuji; Terayama, Hayato; Tanaka, Ryuta; Qu, Ning; Tanaka, Osamu; Umemoto, Kanae; Suyama, Kaori; Sakabe, Kou
Abstract: Introduction: In general, the long head of the biceps brachii (LHB) tendon arises from the supraglenoid tubercle in the shoulder joint, and it has an important stabilizing mechanism for the humeral head in the shoulder joint. This case demonstrates that even if the LHB tendon can be palpated outside of the shoulder joint, it may disappear in the intertubercular sulcus (IS) and in the glenohumeral (GH) joint because of abnormal articulation. Patient concerns: This case involved the cadaver of an 82-year-old Japanese man (number 1936, cause of death: hepatocellular tumor), who was selected from the bodies used for gross anatomy practice at the Tokai University School of Medicine in 2017. Intervention: We removed the fat and skin around the shoulder joint for observational purposes and carefully examined the gross anatomy of the structures. Diagnosis: We suspected that the long head of the biceps brachii tendon arose from the lesser tubercle (LT) in the cadaver. In our case, it was found that the upper part of the subscapularis (SSC) tendon was torn first, and the succeeding degenerative changes and rupture of the LHB tendon were intra-articular. Outcomes: The long head of the biceps brachii tendon was found to be ruptured in the GH joint, and scar tissue developed between the distal stump of the tendon and the articular capsule, resulting in fusion with the LT. Conclusions: This case necessitates confirmation that the LHB tendon is present in the IS and in the GH joint to treat cases wherein failure of the dynamic stabilizing mechanism for the humeral head occurs.